Hubungan Pembelajaran Materi Fiqih Terhadap Peningkatan Kesadaran Melaksanakan Sholat Di Mts Ummul Qur’an Annur Ciomas Kabupaten Bogor - Elsa Mayori; M. Dahlan R. (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Learning is a process of interaction between educators and students that is carried out to help students understand learning well so that changes in behavior arise from students so that they can achieve in terms of cognitive aspects, affective aspects and psychomotor aspects of a student. The learning process emphasizes providing direct experience to develop competencies in order to explore and understand teaching materials naturally. While fiqh is the science that discusses and explains matters relating to the law of syara' which is based on arguments that are understood through the power of ratio. Fiqh subjects are one part of Islamic Religious Education that studies the Fiqh of worship, of course it can be related to the awareness of students in this fiqh material, this awareness itself is a person's ability to know, be aware of everything that exists both within himself and his environment. . The method used in this study is a quantitative method. The results of this study indicate that: 1) Learning Fiqh Materials at MTs Ummul Qur'an Annur Ciomas Bogor Regency is in the Very Good category, the data obtained from the results of the overall average score of the questionnaire is 89 ,85. 2) The awareness approach to praying is in the Good category, the data is obtained from the questionnaire with an overall average value of 90.5. 3) There is a study of fiqh material that has a correlation or relationship to increasing awareness of praying at MTS Ummul Qur'an Annur Ciomas, Bogor Regency. The results of testing this hyphothesis can be seen from the value of the interpretation coefficient. Keywords: Fiqh Material Learning, Awareness of Praying